The roles of nasal nitric oxide in diagnosis and endotypes of chronic rhinosinusitis with nasal polyps - Mengdi Zhu; Xuehuan Gao; Zhuang Zhu; Xiaoqing Hu; Hui Zhou; Jisheng Liu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Chronic rhinosinusitis with polyps (CRSwNP) is a global health concern. Nasal nitric oxide (nNO), a clinical biomarker, have been studied to assess the presence of airway mucosal inflammation. This study aimed to clarify the roles of nNO in diagnosis and endotypes of CRSwNP. Methods Eighty-two CRSwNP patients and thirty healthy volunteers were recruited for this study. The patients were classified into eosinophilic CRSwNP (Eos CRSwNP) and non⁃eosinophilic CRSwNP (Non-Eos CRSwNP) endotypes by tissue eosinophil percentage. nNO levels were measured with an electrochemical sensor-based device. nNO levels and clinical factors were compared among the groups. Receiver-operating characteristic (ROC) curve and logistic regression analyses were performed to evaluate the predictive ability of the nNO for diagnosis and endotypes of CRSwNP. Results Eos CRSwNP patients(143.9 ± 106.2, ppb) had lower nNO levels than Non-Eos CRSwNP(228.3 ± 109.2, ppb, p = 0.013) and healthy subjects(366.5 ± 88, ppb, p < 0.0001). Patients with atopy exhibited significantly higher levers of nNO compared with patients without atopy (p < 0.05). For Eos CRSwNP diagnosis, nNO had high predictive value for Eos CRSwNP (AUC: 0.939; sensitivity: 76.74%; specificity: 96.67%; cut-off value: 231 ppb, p < 0.001). Furthermore, nNO levels were associated with CRSwNP endotypes (odds ratio: 1.010; 95% confidence interval: 1.003, 1.016%; p = 0.002). When the nNO concentration was 158 ppb, we could discriminate Eos CRSwNP from Non-Eos CRSwNP (AUC = 0.710, sensitivity: 76.92%; specificity, 60.47%, P = 0.001). After it was combinated by nNO, peripheral blood eosinophil count (PEAC) and VAS score, the AUC was increased to 0.894 (95%CI = 0.807 to 0.951, p < 0.0001, sensitivity:76.74%, specificity: 89.74%). Conclusions nNO may have potential for non-invasive diagnosis and endotype of CRSwNP. nNO combined with PEAC and VAS score may be a good diagnostic tool for endotyps of Eos CRSwNP. However, the atopic status of the patients influenced the levels of nNO.